Spektrum Keilmuan Pendidikan Teknologi Kejuruan (PTK) Universitas Negeri Padang (Scientific Study) - Mukhaiyar, Riki (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
Education is the core business of LPTK universities in Indonesia, including UNP. And Vocational Technology Education (PTK) is one of two educational disciplines available at UNP. Until now, there has been no defining concept accompanied by a description of the spectrum of expertise that follows from PTK knowledge. This research uses two approaches to develop relevant PTK scientific concepts implemented at UNP. The two methods are the Feynman Technique and the Active Recall method. The Active Recall method is used to strengthen the four steps needed to execute the Feynment Technique. In this research, it was found that there were nine scientific spectra which were used as a complementary puzzle to the integrity of PTK science, namely: PTK Education Philosophy, PTK Education Psychology, PTK Curriculum, PTK Education Evaluation, PTK Education Technology, PTK Education Administration and Supervision, PTK Guidance and Counseling, External Education PTK Schools, and General/Non-Formal PTK Education. With the determination of the PTK scientific spectrum, it is hoped that it will increase the depth and sharpness of scientific studies in PTK.